Foliar nutrients and natural abundance isotope signatures for Larix cajanderi, Cherskiy Density Gradient, Northeast Science Station, Russia, July and September, 2017 - Rebecca Hewitt (Arctic Data Center, 2018)
We quantified foliar nutrients and natural abundance isotope signatures of Larix cajanderi during the peak and the end of the growing season across a gradient of stand densities. We collected foliage from five trees in ten sites across the density gradient near the Northeast Science Station, Russia in July and September 2017. This data set consists of foliar percent carbon, percent nitrogen, natural abundance carbon-13, and nitrogen-15 signatures.